MUATAN INFORMASI (INFORMATION CONTENTS) DARI KEBIJAKAN DIVIDEN - Wirjono, Endang Raino (KINERJA, 2003)
This article has objective to describe information content of dividend policy, especially to foretell earnings growth. It has been oberved that an increase in the price of a stock, while a dividend cut generally leads to a stock price decline. However, many market observers point to the very high fraction of earnings retained (or low dividend payout ratio) as a sign that future earnings growth will be well above historical norm. In the real world, many complications exist that could confound the expected inverse relationship between current payouts and future earnings growth.Keywords: dividend policy, earnings growth, payout ratio